Regeneration of high-silica zeolites after sulfamethoxazole antibiotic adsorption: a combined in situ high-temperature synchrotron X-ray powder diffraction and thermal degradation study. (October 2014) - Leardini, L.; Martucci, A.; Braschi, I.; Blasioli, S.; Quartieri, S.
Abstract: The thermal regeneration of sulfamethoxazole (SMX)-loaded Y and ZSM-5 zeolites was studied using a combined in situ high-temperature synchrotron X-ray powder diffraction and thermal degradation study. The evolution of the structural features was monitored in real time in the 30–575°C temperature range by full-profile Rietveld analysis. SMX thermal degradation pathways into high-silica zeolite antibiotic adducts, as well as the release of evolved species are similar to those for pure SMX. The adsorption/desorption process occurs without any significant loss of zeolite crystallinity, though slight deformations to the channel apertures are observed. Regenerated zeolites regain almost perfectly 'bare' (i.e. unloaded) material unit-cell parameters and only a slight memory effect, in terms of structural deformations induced by the process, is registered in the channel geometry. Interestingly, these changes do not affect the adsorption properties of the regenerated samples, which are able to re-adsorb comparable amounts of antibiotic molecules as in the first adsorption cycle.